Instagram @Jakartabiennale Sebagai Media Promosi Dalam Pelaksanaan Exhibition Jakarta Biennale 2021 “ESOK” - Khotimah, Wininda Qusnul; Agustini, Vilya Dwi (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
The Use of Instagram as a Promotional Tool for the 2021 “ESOK” Jakarta Biennale Exhibitions. The Jakarta Biennale has been using the Instagram feature to help promote exhibitions by the Museum of Indonesia National Awakening (Museum Kebangkitan Nasional) for some time. The collection was considered a dormant tourist destination that needs to be reactivated. This research elaborates on how the official account @jakartabienalle projects promotional content about the event. Using the content marketing theory, we employ content analysis methods to describe the promotions' narratives spectrum qualitatively. Complementary to that, we also conducted in-depth interviews, observations, and documentation upon the account followers. We found a specific trace of the “ESOK” signature in the upper-left part of every post. Along with that, a two-long paragraph caption also completes the picture-based pieces of information that consist of registration pieces of information and details of the pictures. Finally, we also conclude that hashtags and geotagging features play an essential part in helping audiences locate the event.